2019
DOI: 10.1038/s41598-019-51571-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of mountainous meadows associated with biodiversity attributes, perceived health benefits and cultural ecosystem services

Abstract: Associations between biodiversity, human health and well-being have never been discussed with reference to agriculturally managed, species-rich mountainous meadows. We evaluated these associations between extensively managed (one mowing a year, no fertilization) and abandoned (no mowing since more than 80 years, no fertilization) semi-dry meadows located in the Austrian and Swiss Alps. We quantified the richness and abundance of plants, grasshoppers, true bugs, bumblebees, syrphids and landscape characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…In the general climate of abandonment that rural and mountainous areas have been undergoing in the past decades, not limited to the Apennines, but well-documented especially in Eastern Europe [88][89][90], it is thus imperative to look to these traditions and to involve the people who are custodians of ecological knowledge in order to safeguard both biological and cultural diversity. Well-preserved landscapes would also have a positive effect on tourism in these areas, as it has been shown that managed grasslands are more attractive and have better visibility than abandoned landscapes [61,91]. This type of pastoralism is kept alive by the cultural traditions tied to it, more so than by some type of economic benefit, even though areas with more widespread agrienvironmental schemes are less likely to be abandoned [90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general climate of abandonment that rural and mountainous areas have been undergoing in the past decades, not limited to the Apennines, but well-documented especially in Eastern Europe [88][89][90], it is thus imperative to look to these traditions and to involve the people who are custodians of ecological knowledge in order to safeguard both biological and cultural diversity. Well-preserved landscapes would also have a positive effect on tourism in these areas, as it has been shown that managed grasslands are more attractive and have better visibility than abandoned landscapes [61,91]. This type of pastoralism is kept alive by the cultural traditions tied to it, more so than by some type of economic benefit, even though areas with more widespread agrienvironmental schemes are less likely to be abandoned [90].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the last decades, widespread rural depopulation has induced the loss of different human activities tied to agriculture, traditions, festivals, and pastoralism [23,57,58], as well as loss of cultural identity [59,60] and of desirability of abandoned and unmanaged landscapes, which are perceived to be "less natural" [61]. Thus, the phenomenon of rural abandonment is doubly impactful, on both the natural as well as the cultural diversity of mountainous regions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, secondary succession is hindered. These methods are commonly used as a way to protect landscape and biodiversity in mountainous areas where traditional grazing was typical [73,74]. These activities have been conducted in Radziechowska glade for a few years.…”
Section: Discussionmentioning
confidence: 99%
“…managed forest, forest bathing, forest walking, etc., have been implemented in some of the studied countries, and positively affected the psychological and physiological status of participants and visitors (Bielinis et al 2018;Bielinis et al 2019aBielinis et al , 2020Hussain et al 2019;Janeczko et al 2020;Rathmann et al 2020). The positive effect of spending leisure time in the forest and by outdoor activities was observed in different age groups, from young age (Kimic & Kundziewicz 2020) and young adults (Bielinis et al 2018;Bielinis et al 2019a;Hussain et al 2019;Janeczko et al 2020An overview of the findings shows the contribution of the forests to the human physical and mental health. Development of infrastructures and policy harmonization that enable the forests to perform their services optimally are encouraged in countries where such forest recreation and education still do not exist.…”
Section: Scopus Publicationsmentioning
confidence: 99%